Diabetic retinopathy and the use of laser photocoagulation: is it cost-effective to treat early?. Issue 1 (25th September 2017) - Mistry, Hema; Auguste, Peter; Lois, Noemi; Waugh, Norman
Abstract : Background/aims: The aim of the study was to explore whether it would be cost-effective to apply panretinal photocoagulation (PRP) at the severe non-proliferative diabetic retinopathy (NPDR) (early treatment) stage, compared with waiting until high-risk proliferative diabetic retinopathy (HR-PDR) characteristics (deferred treatment) developed. Methods: A Markov model with a 30-year time horizon was developed, in which patients presenting with moderate NPDR could progress through all stages of DR (severe NPDR>early PDR>HR-PDR>severe PDR) to severe vision loss and blindness (and to death). A National Health Service and personal social services perspective was adopted. Transition probabilities were mainly derived from the Early Treatment Diabetic Retinopathy Study. Health state utilities, costs and complications were based on information from the literature, supplemented by expert opinion. Costs and outcomes were discounted at 3.5%. Both deterministic and probabilistic sensitivity analyses were conducted. Results: Administering PRP at the severe NPDR stage could be more effective and less costly than waiting until HR-PDR developed. Sensitivity analyses gave similar results, with early treatment continuing to dominate deferred treatment. The probabilistic sensitivity analysis suggests that at willingness-to-pay threshold of £20–£30 000 per quality-adjusted life year, the probability of early treatment being cost-effective is 60%. Conclusion: PRP administered at the severe NPDR stage is likely to be cost-effective compared with delaying photocoagulation until HR-PDR develops. However, given the limitations of the evidence, these results need to be interpreted with caution. A trial of early versus deferred laser therapy is needed to provide better data based on modern treatments.